METHODS OF INCREASING PHYSICAL FITNESS OF STUDENTS THROUGH A FOUR-LEVEL LADDER OF PHYSICAL ACTIVITY (Scientific journal of the Fergana State University, 2024)
The "Four-Level Physical Training Ladder" presents a novel and versatile approach to enhancing the physical fitness of students in general education schools. Developed and patented in the Republic of Uzbekistan (No. sap 02411), this innovative training device is designed to integrate seamlessly into both extracurricular activities and standard physical education classes. The ladder is divided into four distinct zones, each tailored to specific age groups ranging from 7 to 17 years, with each zone having steps of varying heights (0.33 cm to 0.44 cm) and colors (white, green, yellow, red). This allows for a broad range of exercises, adaptable to different physical abilities and developmental stages. The ladder's design emphasizes functional and constructive flexibility, facilitating a wide variety of exercises that cater to the improvement of cardiovascular health, strength, and overall movement readiness. Implemented three times a week, this method provides a structured yet dynamic environment for physical development, enhancing designed students' fitness levels through a carefully mix of special and auxiliary exercises. The "Four-Level Physical Training Ladder" represents an innovative step forward in physical education, combining practicality, adaptability, and effectiveness in a single training tool.